β-Arrestin1 Promotes Colorectal Cancer Metastasis Through GSK-3β/β-Catenin Signaling- Mediated Epithelial-to-Mesenchymal Transition - Song, Qing; Han, Zhifen; Wu, Xinnan; Wang, Yan; Zhou, Lihong; Yang, Liu; Liu, Ningning; Sui, Hua; Cai, Jianfeng; Ji, Qing; Li, Qi (Frontiers in Cell and Developmental Biology, 2021)
Recurrence and metastasis seriously affects the prognosis of patients with tumors, and the epithelial-to-mesenchymal transition (EMT) plays a key role in promoting tumor invasion and metastasis. Previous studies have showed that β-arrestin1 acted as a tumor-promoting factor in multiple types of tumor. However, the exact role and mechanism of β-arrestin1 in colorectal cancer (CRC) progression remains to be elucidated. Our research aimed to explore the potential mechanism underlying the role of β-arrestin1 in CRC metastasis. The expression of β-arrestin1 was investigated in both primary and metastatic CRC tissues using the GSE41258 database, and it was revealed that CRC patients with liver/lung metastasis had a higher expression level of β-arrestin1, and the expression level of β-arrestin1 was inversely correlated with the prognosis of CRC patients. Further in vitro mechanism studies indicated that β-arrestin1 had the ability to promote the migration of CRC cells through regulating the EMT process by activating Wingless/integration-1 (Wnt)/β-catenin signaling pathways. Blocking Wnt/β-catenin signaling with inhibitor ICG001 decreased the promoting effect of β-arrestin1 on EMT in CRC. In vivo imaging experiments further demonstrated the promoting effect of β-arrestin1 on the lung metastasis of CRC cells by tail vein injection in mice. The results of this paper suggest that β-arrestin1 promotes EMT via Wnt/β-catenin signaling pathway in CRC metastasis, and provides a novel therapeutic target for CRC metastasis.